Obesity and chronic kidney disease: prevalence, mechanism, and management - Hyung Eun Yim; Kee Hwan Yoo (The Korean Pediatric Society, 2021)
The prevalence of childhood obesity is increasing worldwide at an alarming rate. While obesity is known to increase a variety of cardiovascular and metabolic diseases, it also acts as a risk factor for the development and progression of chronic kidney disease (CKD). During childhood and adolescence, severe obesity is associated with an increased prevalence and incidence of the early stages of kidney disease. Importantly, children born to obese mothers are also at increased risk of developing obesity and CKD later in life. The potential mechanisms underlying the association between obesity and CKD include hemodynamic factors, metabolic effects, and lipid nephrotoxicity. Weight reduction via increased physical activity, caloric restriction, treatment with angiotensin-converting enzyme inhibitors, and judicious bariatric surgery can be used to control obesity and obesity-related kidney disease. Preventive strategies to halt the obesity epidemic in the healthcare community are needed to reduce the widespread deleterious consequences of obesity including CKD development and progression.